Regulating developers contributions through planning agreements for promoting sustainable development in Malaysia - Maidin, Ainul Jaria; Sulaiman, Siti Sarah (American Scientific Publishers, 2017)
The local authorities are given the key role to plan and control development activities for the primary purpose of contributing to the growth of the economy, social prosperity and promoting sustainable development within their local authority areas. This is achieved through their planning, economic and sustainable development functions directed by policies and empowered by law. Pursuing sustainable development involves seeking positive improvements in the quality of the built, natural and historic environment, as well as in people’s quality of life, employment opportunities; replacing with environmental friendly designs; improving the conditions in which people live, work, travel and leisure and widening the choice of high quality homes and others depending on the changing needs of the society. The successful implementation of the plans to promote sustainable development requires strong financial commitment. Since independence, the local authority has been relying on the property developers’ contributions in providing critical resources to facilitate the funding of physical and social infrastructure and the financial support needed by the local authorities. This funding is secured through informal negotiation for the contributions to be made by the developer through Planning Agreements. The informal practice of Planning Agreements within the development control system was part of a developer contribution system besides the imposition of conditions attached to a grant of planning permission. The practitioners and industry opinion has been mixed regarding how Planning Agreements are being negotiated and used, making them the most controversial development contribution mechanism. This research analysed the objectives for the planning agreements, and whether there is a need to regulate the informal practice that can lead to improved infrastructure development and promote sustainable development. A case study of the practice in the Shah Alam City Council is analysed to present the Planning Agreement system in place. The paper seeks to propose recommendations on the need to introduce legal measures to promote good governance of the present system.